Synthesis of InSb nanocrystals in an air atmosphere and their photocatalytic activity from near-infrared to ultra-violet - Kasidid Yaemsunthorn (2018)
© 2017 Elsevier Ltd We report a new facile route to prepare indium antimonide (InSb) nanocrystals (NCs) in air and at ambient pressure. Spherical cubic zinc blende InSb NCs with an average size of 5 nm were synthesized and spontaneously separated through a rapid microwave-assisted one-pot reaction. The photocatalytic activity of obtained product was investigated by the decolorization of methyl orange dye under near-IR, visible light, and UV irradiation. This novel synthetic pathway may improve existing applications and suggest new opportunities for studying III-V semiconductor nanomaterials.